2019
DOI: 10.1016/s0140-6736(19)30985-7
|View full text |Cite
|
Sign up to set email alerts
|

Why now for a Series on gender equality, norms, and health?

Abstract: When this Series on gender equality, norms, and health was first conceptualised in 2015, we were surprised by how little targeted effort had been achieved at this intersection, despite compelling evidence that gender equality improves health and wellbeing. 1,2 The 2030 Agenda for Sustainable Development and universal health coverage goals demand greater attention to the social determinants of health, including gender, and more integrated, multisectoral programming to enable all people to reach their full human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 6 publications
0
25
0
Order By: Relevance
“…The Lancet series ‘Gender Equality, Norms, and Health’ [ 1 ] highlights the importance of treating sex and gender as distinct, not interchangeable, entities in medical research. While sex includes the biological distinction between men and women, gender adds to the behavioral, cultural or psychological attributes associated with one sex or the other according to societal norms, which can change over time and differ among cultures [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Lancet series ‘Gender Equality, Norms, and Health’ [ 1 ] highlights the importance of treating sex and gender as distinct, not interchangeable, entities in medical research. While sex includes the biological distinction between men and women, gender adds to the behavioral, cultural or psychological attributes associated with one sex or the other according to societal norms, which can change over time and differ among cultures [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…While data availability may be partially determined by local systems and may vary depending on the income level of a country; it is suggested that future studies collect non-binary data and consider intersections with other social stratifiers. Other studies have also raised the lack of clarity in the use of sex and gender concepts and the reliance on binaries [24,25,28,32,33]. Findings also show that little is reported about the content of communication materials and of data collection tools used, which limits understanding of how these have responded to the local context and their possible effects.…”
Section: Strengths and Limitations Of Interventionsmentioning
confidence: 99%
“…From inception to completion, collect, interpret, and report data by sex and gender. Guidelines for integration of sex and intersectional gender into data collection, analysis, and reporting exist [31,112], as well as studies providing foundational concepts to understand how sex and gender concepts differ and overlap [24,25,28,32].…”
Section: Recommendations For Interventionsmentioning
confidence: 99%
See 2 more Smart Citations